Mutations Associated with Acquired Resistance to PD-1 Blockade in Melanoma - Zaretsky, Jesse M; Garcia-Diaz, Angel; Shin, Daniel S; Escuin-Ordinas, Helena; Hugo, Willy; Hu-Lieskovan, Siwen; Torrejon, Davis Y; Abril-Rodriguez, Gabriel; Sandoval, Salemiz; Barthly, Lucas; Saco, Justin; Homet Moreno, Blanca; et al. (The New England journal of medicine, 2016)
Whole-exome sequencing was performed on four patients' tumors before exposure to pembrolizumab and after disease progression following a response to treatment. Acquired mutations involving antigen presentation and interferon response were noted. Durable responses in metastatic cancers have been achieved with a variety of immunotherapies such as interleukin-2, adoptive cell transfer of tumor-infiltrating lymphocytes, antibodies that block cytotoxic T-lymphocyte–associated antigen 4 (CTLA4), 1 – 5 and antibodies that block programmed death 1 (PD-1). 6 – 10 However, in a recent study, approximately 25% of patients with melanoma who had had an objective response to PD-1 blockade therapy had disease progression at a median follow-up of 21 months. 11 The mechanisms of immune-resistant cancer progression are mostly unknown. Previous studies involving humans examined the loss of beta-2-microglobulin as a mechanism of acquired resistance to several forms of cancer . . .